If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (c + -3)(c + -3) = o Reorder the terms: (-3 + c)(c + -3) = o Reorder the terms: (-3 + c)(-3 + c) = o Multiply (-3 + c) * (-3 + c) (-3(-3 + c) + c(-3 + c)) = o ((-3 * -3 + c * -3) + c(-3 + c)) = o ((9 + -3c) + c(-3 + c)) = o (9 + -3c + (-3 * c + c * c)) = o (9 + -3c + (-3c + c2)) = o Combine like terms: -3c + -3c = -6c (9 + -6c + c2) = o Solving 9 + -6c + c2 = o Solving for variable 'c'. Combine like terms: o + -1o = 0 9 + -6c + c2 + -1o = 0 The solution to this equation could not be determined.
| x+4=9x-72 | | 9(3+x)= | | 27y^2-52y+25= | | 66.8=2x+4.7 | | 5p-(4p-4)=17 | | 19.8=x+2.9+4.5+x | | 9.9x+38.57=-10.1+38.41 | | 15(x+1)=5(4x) | | y=zr | | p=0.4+-350.002x | | 2w^9-20w^8-48w^7= | | p=1.4+-350x-1+-0.002x | | 1(t-4)+7t=4(2t+3)-8 | | 15x+15=20x | | p(x)=-0.002x^2+1.4x-350 | | 7.4x-2.9=11.9 | | 1.95x-4.38z+2.83a-5.21z-9.27x= | | v+(v-16)+3(30-v)=641 | | 3a+4=24 | | h=32+14t-1+-16t | | -(6x+3)-(-5x-8)=3 | | (9-x)(3x+5)=0 | | -x-18+2x+4=6x+24 | | a-6b+2c+a-6b+n-2c= | | 9y+3=27 | | 4b+25=9b | | 6(4-1)-5(z+8)=16(z+1) | | y=-(1)-3 | | y=-(0)-3 | | y=-(-1)-3 | | 4b+5x=2x | | -8(t-5)-(t+4)=9 |